PENDIDIKAN KEAGAMAAN BAGI ANAK PEREMPUAN DI JORONG GUNUNG KECAMATAN TANJUNG BARU KABUPATEN TANAH DATAR - Hendrisab (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2018)
The problem in this discussion is that girls who graduate from primary school(SD) most of them only continue or continue their education education level that hasa very shallow Islamic educational content, should the girls continue educationeducation level that has a higher content of Islamic education because this Islamiceducation will lead children into a child who knows with his god, as well as the rightsand obligations as a caliph in the earth. Especially for girls who later they willbecome a mother and who will educate their children, because the time spanpossessed by a mother to educate her child in a day more than with a span of timeowned by a father or father against his son, by Therefore, the role of a woman isneeded for future generations. The purpose of this research is to know the interest ofparents to the education of Islamic religion of girls in Kanagarian Gunung,Kec.Tanjung Baru, Kab. Tanah Datar. As well as the mastery of the deeds of thedaughters of worship, and the factors influencing the promotion of religiouseducation of girls.